Studi Komparatif Aktivitas Belajar Siswa antara Moving Class dengan Kelas Menetap Fase F di SMA Semen Padang - Aulia, A'isyah; Ernawati, Ernawati (ALSYS, 2025)
The learning system in secondary schools has changed with the implementation of the moving class method which allows students to move classes according to the subject. This study aims to compare student learning activities between the moving class system and sedentary classes at Semen Padang High School. The research method used is comparative with a quantitative approach. The research sample consisted of two classes, namely XII 2 class (sedentary class) and Geography 3 class (moving class), which were selected by purposive sampling technique. Data were collected through observation, documentation, and Likert scale-based questionnaires. The results showed that the average student learning activity in the moving class system was higher than the sedentary class. The most prominent indicators in the moving class are motor and mental activities, while the sedentary class is more dominant in writing activities. The independent sample t-test statistical test showed a significant difference between the two learning systems (sig. 0.002 <0.05). This finding indicates that moving class is more effective in increasing student engagement in learning, although there are obstacles such as fatigue due to class movement. Therefore, it is necessary to improve supporting facilities and time management strategies so that the moving class system can run more optimally.